A Case Study of Students’ Speaking Anxiety in Learning English in the Classroom - Rohmah, Faidotur; Mohammad Kurdi Wijaya (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2025)
Anxiety is a major concern in the learning of speaking by EFL learners in an instructed language instruction situation. Speaking anxiety, despite being extensively studied, has yet to be fully understood. Keeping this in mind, this study explores the reasons of anxiety among foreign language learners, with special reference to "speaking" as a skill. Speaking is one of the abilities that appear to represent the students are able to speak English. Unfortunately, the majority of Indonesian students, particularly those at the university level, lack the necessary skills to communicate effectively in English. Students in the 4.0 era are expected to have strong communication skills and the capacity to interact with their peers. Speaking also demands practice and a strong psychological pleasure that must be pleasant. A related study that enhances the efficacy of speaking in language teaching and learning is critical. This descriptive study discusses the significance of good communication in English as a foreign language. The purpose of this study is to look into the speaking anxiety of MTs Roudlotut Tholibin eighth grade students. The specific goal of this study is to look into the variables that affect students' speaking anxiety as well as methods for reducing it based on the students' personal experiences. There were five students were chosen to participate. The researcher interviewed students who experience anxiety when speaking English, using a descriptive qualitative method with a phenomenological approach. Two factors were revealed by the results. They are internal and external factors. English teachers need to comprehend the personalities of each of their students in the classroom, as each student's anxiety level can differ from one another.